On the Optimal Size of Public Employment - Anna Carolina dos Reis; Eduardo Zilberman (Pontifícia Universidade Católica do Rio de Janeiro (PUC-Rio), Departamento de Economia, 2013)
A public job can be seen as a source of insurance against income risk. Indeed, many public employees have job stability, which is compounded with less volatile and more compressed wages. Hence, by increasing its number of public employees, the government enhances the overall degree of insurance in the economy. In this paper, we introduce public employment in a standard incomplete markets model with overlapping generations. The aim is to explore the welfare gains or losses due to a larger government, accounting for this extra source of insurance. In a model economy calibrated to Brazil, where public employment is around 13.5 percent of the workforce, we find that if the government relies on consumption taxes to balance its budget, the optimal size of public employment is nearly flat, ranging from 8 to 12 percent of the workforce. However, if the public employment is reduced from 12 to 8 percent, welfare losses due to a reduction in the degree of insurance are 2 percent, which are compensated by welfare gains due to level and inequality effects. This insurance effect is robust to a missepecification of the production technology associated with the public sector
Keywords: D31; E24; H11; 330; pubic employment; insurance; incomplete markets; optimal policy.